Analysis of Service Quality and Facilities on Parents Interest in Enrolling Their Children at Sumbakeling Public Elementary School Kuningan Regency With Word of Mouth as an Intervening Variable - Rizky Aditya (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: Education plays a crucial role in improving human resources quality by developing individuals’ knowledge, skills, values and attitudes. The government is currently focusing on enhancing quality, ensuring equity, digitalizing learning and revitalizing school facilities. Background Problems: Sumbakeling Public Elementary School in Kuningan Regency is a focal point of both central and regional educational policies. A phenomenon has emerged in which parents’ interest in enrolling their children has declined due to perceptions of inadequate school services and facilities. Aspects such as teacher services, administration, classroom facilities, library and the overall environment are still considered suboptimal. Research Methods: The research data were analyzed using SEM-PLS with Smart PLS 4.0 software. The population in this study consists of all parents of students at Sumbakeling Public Elementary School in Kuningan Regency whose children are registered as active students until October 2025, totaling 86 parents. The sampling technique used in this study was Purposive Sampling where the sample was selected based on specific considerations from the researcher that were most relevant or met the criteria namely 42 parents out of the 86 students. Finding/Results: Results indicate that service quality and facilities each have a positive and significant effect on word of mouth and parents’ interest. Word of mouth also positively and significantly influences parents’ interest. Furthermore, both service quality and facilities significantly affect parents’ interest through the mediating role of word of mouth.. Conclusion: All variables in the research model have a positive and significant influence on each other. Efforts to improve services, facilities and the positive experiences of parents should be carried out continuously to increase parents’ interest in enrolling their children in school.